Changes in soft and hard tissue of central incisor before and after distal migration of the maxillary dentition in adult patients with different periodontal phenotypes - CHEN Rui, HAN Shuang, AN Qi (口腔疾病防治)
Objective To explore the changes of periodontal soft and hard tissue parameters of the maxillary central incisors after the distant migration of the maxillary total dentition in adult patients with different periodontal phenotypes, so as to provide a reference for orthodontic treatment. Methods The study was approved by the hospital ethics committee, and the patients signed the informed consent form. Fifty-two adult patients in the orthodontic department of Hefei Stomatological Hospital were selected and divided into thick gingival and thin gingival groups, with 26 cases in each group. The labial and palatal alveolar bone parameters and various periodontal indexes of the maxillary central incisor teeth of the two groups were collected and recorded before and after treatment. SPSS 26.0 statistical software was used to statistically analyze the intra-group and inter-group differences. Results After orthodontic treatment, the differences in sella-nasion-subspinale angle (SNA), sella-nasion-supramental angle (SNB), and subspinale-nasion-supramental angle (ANB) were not statistically significant (P > 0.05). However, the inclination of the upper middle incisor teeth (U1-NA) decreased significantly (P < 0.05), and there was no significant difference in SNA, SNB, ANB, and U1-NA between the two groups after treatment (P > 0.05). The thickness of the labial alveolar bone of the maxillary central incisors in both groups increased at the labial neck 1/3 and labial middle 1/3 (P < 0.05), and decreased at the apical 1/3 (P < 0.05). The thickness of the palatal alveolar bone decreased at the labial neck 1/3 and labial middle 1/3 (P < 0.01), and increased at the apical 1/3 (P < 0.01). In both groups, the height of the lip and palate of the upper jaw decreased to different degrees, and the height of the palatal alveolar bone was lower in the thin gingival group (P < 0.05). There were no significant differences in maxillary central incisor probing depth (PD), lip keratinized tissue width (KTW), or lip gingival recession (GR) between the two groups after treatment (P > 0.05). Conclusion In the process of maxillary central incisor adduction, the labial-palatine alveolar bone remodeling is not uniform, and the alveolar bone of palatine side is mainly absorbed, which should be paid attention to clinically. Palatal alveolar bone height decreased more significantly in patients with thin gingiva after orthodontic treatment, and the risk of bone fenestration and bone dehiscence was greater.